Manajemen Digitalisasi Sekolah Untuk Meningkatkan Mutu Akademik Di SMA Negeri 1 Karangrayung - Marginingsih, Peni; Kusumaningsih, Widya; Violinda, Qristin (Cetta: Jurnal Ilmu Pendidikan, 2025)
The Industrial Revolution 4.0 has brought major changes in various fields, including education, by triggering significant innovation and digital transformation. The Ministry of Education and Culture (Kemendikbud) launched a school digitalization program as an effort to prepare human resources to face the industrial revolution 4.0. School digitalization is an intervention that encourages the provision of fast, automatic, and open services so that they can be in line with current technological and information developments and not be left behind by other countries.This study aims to describe and analyze the planning, organization, implementation, evaluation of school digitalization to improve academic quality at SMAN 1 Karangrayung. In this study, the informants selected with a total of 23 people consisting of the Principal, 2 Vice Principal, 8Teachers and 12 Students. This study uses a qualitative approach using observation, interview and documentation methods for data collection. The data analysis technique in this study uses quantitative descriptive. Based on the results of the study, the Planning carried out by SMA Negeri 1 Karangrayung in carrying out school digitalization management to improve academic quality is fairly good. There are five components in the planning stage, namely planning goals, researching problems and work, collecting data and information, determining the management stage, formulating problem solving. For organizing there are three components, namely effective division of labor, team formation, and implementation of meetings. For Implementation there are five components, namely determining the start of implementation, providing examples, providing motivation, communicating the entire direction of work, fostering school digitalization management. For Evaluation there are four components, namely determining standards or basis for supervising, and measuring the implementation of teacher work, comparing implementation with standards, taking corrective actions.